Estresores parentales en la Unidad de Cuidados Intensivos Neonatales del Hospital General Isidro Ayora, de la provincia de Loja - Zhinin Illescas, Víctor Leodan (2019)
The arrival of a newborn brings a series of changes that generate concern and more when it presents an alteration in health that warrants hospitalization, causing stress in the parents. Therefore, the present research work, "Parental Stressors in the Neonatal Intensive Care Unit of the General Hospital Isidro Ayora, of the Province of Loja", was proposed, whose objective was to determine the parental stressors in the aforementioned service, for which carried out a descriptive and cross-sectional quantitative study, a survey was applied to 122 parents, using the Maternal Stress Scale (EEM) adapted to the purposes of this research, therefore the percentage analysis of data was carried out using the program Excel As a result it was found that the main stressors for parents with newborns hospitalized in the Neonatal Intensive Care Unit are: the constant noise of the monitors and equipment, the unusual color of the newborn, the separation with the newborn and in Regarding communication with the staff, the criterion that explains things too quickly stands out. Regarding the level of parental stress, it was determined that 32% of parents have an excessive level of stress, 25% a moderate level of stress, 20% a level of mild stress and 23% without stress. Finally, an educational triptych was delivered in order to inform the beneficiary group about the operation of the Neonatal Intensive Care Unit. Keywords: parents, hospitalization, stress, neonate